Scaffolds with Magnetic Nanoparticles for Tissue Stimulation - Leal-Marin Sara; Gallaway Glynn; Höltje Kai; Lopera-Sepulveda Alex; Glasmacher Birgit; Gryshkov Oleksandr (Current Directions in Biomedical Engineering, 2021)
Magnetic nanoparticles (MNPs) have been used in several medical applications, including targeted hyperthermia, resonance tomography, diagnostic sensors, and localized drug delivery. Further applications of magnetic field manipulation through MNPs in tissue engineering have been described. The current study aims to develop tissue-engineered polymeric scaffolds with incorporated MNPs for applications that require stimulation of the tissues such as nerves, muscles, or heart. Electrospun scaffolds were obtained using 14%w/v polycaprolactone (PCL) in 2,2,2-Trifluoroethanol (TFE) at concentrations of 5% & 7.5%w/v of dispersed MNPs (iron oxide, Fe3O4, or cobalt iron oxide, CoFe2O4). Scaffolds were analyzed using scanning electron microscopy (SEM), energy dispersive x-ray spectroscopy, uniaxial tensile testing, and cell seeding for biocompatibility. Human bone marrow mesenchymal stem cells (bmMSCs) were seeded on the scaffolds. Biocompatibility was assessed by metabolic activity with Resazurin reduction assay on day 1, 3, 7, 10. Cell-cell and cell-scaffold interactions were analyzed by SEM. Electrospun scaffolds containing MNPs showed a decrease in fiber diameter as compared to scaffolds of pure PCL. The maximum force increases with the inclusion of MNPs, with higher values revealed for iron oxide. The metabolic activity decreased with MNPs, especially for cobalt iron oxide at a higher concentration. On the other hand, the cells developed good cell-scaffold and cell-cell interactions, making the proposed scaffolds good prospects for potential use in tissue stimulation.